Pelatihan Pelatihan Mitigasi Bencana untuk Peningkatan Pengetahuan & Sikap Masyarakat dalam Menghadapi Letusan Gunung Kelud: Disaster Mitigation Training to Improve Community Knowledge and Attitudes in Dealing with the Mount Kelud Eruption - Margaretta, Sheylla Septina; Santoso, Winanda Rizki Bagus; Sumaningrum, Ningsih Dewi (Universitas Negeri Surabaya, 2024)
Sugihwaras Village is located in the area closest to G. Kelud which is an active volcano with the potential to erupt. The eruption had an impact on physical, psychological, economic and material disturbances. The lack of knowledge of the population about disaster mitigation and the absence of a standby volunteer forum are the partners' main problems. This community service aims to form a G. Kelud alert volunteer forum and increase the knowledge and attitude of the community in preparing for volcanic eruptions through G. Kelud disaster mitigation training. The result of this community service is the formation of the G.Kelud standby volunteer forum and there is an increase in knowledge with the result that before being given training the majority of 32 (58.1%) were in the less category and after being given disaster simulation training it increased with the majority score being 34 (61.8%) the most in the good category. This is also in line with the attitude of the partner community in dealing with the Mount Kelud eruption disaster which has increased, from before being given training the majority of 45 (81.81%) had a negative attitude and after being given training it increased with a majority value of 47 (85.45%) having a positive attitude in dealing with the eruption of G. Kelud. So it can be concluded that the formation of the G.Kelud standby volunteer forum and disaster mitigation training can increase the knowledge and attitude of the community in disaster preparedness. Keywords: Disaster mitigation; Knowledge; Attitude